DEVELOPMENT OF PROBLEM-BASED ENGLISH MATHEMATICS WORKSHEETS FOR INFORMATICS STUDENTS - Risa Santoso; Lilis Widayanti; Widya Adhariyanty Rahayu (INOVISH JOURNAL, 2021)
Mathematics and English can collaborate so that the students in practice on computers are also familiar with mathematical terms in English. This will help the ability of informatics students to understand other materials in the informatics study program. The fact that occurs in learning mathematics and English at Institut Asia campus is that students are still less enthusiastic in pursuing these subjects so that the majority of students have not achieved optimal learning outcomes. In collaborating the English and Math course in learning, the instructional needs learning tools that can help. One of the learning tools needed is teaching materials such as worksheets. The worksheet that will be developed uses a Problem Based Learning approach. The development model adopted is Plomp’s development model which consists of 3 stages, namely preliminary research, prototyping, and assessment phase. The developed math worksheets will meet the criteria of validity, practicality, and effectiveness. Based on the validation test, the score obtained shows that the mathematics worksheet is in the proper category. While the results of the effectiveness test and the results of student responses showed a score of 80.35 and 76.76 or in the effective category and quite feasible.